THE ROLE OF RELIGION IN THE CONSTITUTIONS OF INDONESIA AND PAKISTAN: COMPARISON OF ISLAMIC CONSTITUTIONAL LAW (Faculty of Law, Universitas 17 Agustus 1945 Surabaya, 2022)
The purpose of knowing the position of religion in the state constitution is to know how to protect human rights and what are the noble values ​​that regulate the lives of citizens, therefore religion in the constitution is one of the benchmarks for the administration of the state, constitutional norms place religion to occupy the important in the life of the state so that another consequence of the implementation of religious values ​​in the state is the policies of state officials and the behavior of citizens should not conflict with religious values. This study uses a normative approach and uses a qualitative analysis methodology with data collection techniques through literature studies such as legislation, books, legal journals, and online media. The results of the analysis show that in terms of the constitutions in Indonesia and Pakistan, there are several basic differences, starting from the use of norms, state institutions, government systems, social pluralism, and the implementation of the constitution considering that Indonesia is not an Islamic country while Pakistan is an Islamic country but there are still some similarities. between Indonesia and Pakistan, but this shows that if only religion is used in the constitution without paying attention to the social, economic, political, and cultural needs of the community, this will become a big problem so it will need to share